How do clinicians with different training backgrounds manage walk-in patients in the ED setting?. Issue 12 (16th April 2014) - Harris, Tim; McDonald, Keith
Abstract : Objective: To compare the initial assessment and management of walk-in emergency department (ED) patients between different types of healthcare providers. Setting: A large teaching hospital with an annual ED census of 140 000 adult patients. Methods: A random sample of 384 patients who self-presented to the ED was obtained. A detailed analysis of each patient record was performed by two clinicians. Data were obtained on the presenting condition, and disposition of each patient, either into the ED for further assessment, or discharge. Results: GPs were significantly more likely to discharge patients home as compared to emergency nurses. ED senior nurses were more likely than GPs to stream patients into the ED for further assessment. Of the patients referred into the ED for further assessment by senior ED nurses, the majority were discharged home. There were insufficient numbers of emergency physician assessments for meaningful statistical analysis. Conclusions: The clinician groups studied here demonstrated different patterns of discharge and referral, reflecting their training and experience. When planning operational procedures, the training and background of the staff allocated to each area should be considered.